Honouring age the social dynamics of age structure in 1 Timothy - LaFosse, Mona Tokarek (Montreal McGill-Queen's University Press, 2024)
Exploring age, intergenerational relationships, and the social power of reputation across ancient Mediterranean cultural contexts, Honouring Age positions age as an essential aspect of communal identity and familial roles in the early Christian experience as represented in one of the most contentious texts in the New Testament, 1 Timothy.
Cover -- HONOURING AGE -- Title -- Copyright -- Dedication -- Contents -- Table and Figures -- Acknowledgments -- A Note on Ancient Sources -- 1 Why Study Age in 1 Timothy? -- 2 Mediterranean Dynamics of Age Structure and 1 Timothy -- 3 One Letter, Two Stories: Rhetoric and Crisis -- 4 Ideal Behaviour in the "Household of God" (1 Tim. 5:1-2) -- 5 Categorizing Widows: Definitions and Responsibilities -- 6 Why Sixty? -- 7 Younger Widows and Age Hierarchy among Women -- 8 A Believing Woman -- 9 Elders -- 10 Intergenerational Conflict in 1 Timothy: The Big Picture -- 11 The Visibility of Age -- Notes -- References -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Bible; Bible.-Timothy, 1st-Criticism, interpretation, etc; Age groups; Relations entre générations; Vieillesse; Vieillesse - Enseignement biblique; Veuves - Enseignement biblique; Old Age; Age groups; Criticism, interpretation, etc; History; Mediterranean Region